Dynamics of population of gadolinium-156 nuclei energy levels during neutron pumping of isotope-modified gadolinium oxide; Proceedings of SPIE; Vol. 11322 : Pulsed Lasers and Laser Applications (AMPL-2019) - Shamanin I. V. Igor Vladimirovich; Kazaryan M. A. Mishik Ayrazatovich; Bedenko S. V. Sergey Vladimirovich; Knyshev V. V. Vladimir Vladimirovich; Shamanin V. I. Vitaly Igorevich (Biophotonics, 2019)
Title screen